PENINGKATAN KEMAMPUAN MEMBACA INTENSIF DENGAN MENGGUNAKAN METODE SQ3R PADA SISWA KELAS IIA SDN 23 MARAPALAM KOTA PADANG - shintia, putri; sukma, Elfia; Amini, Risda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to describe the students’ intensive reading skill through the use of the SQ3R method in Grade III A of Elementary School Number 23 Marapalam, Padang. This is a classroom action research with qualitative and quantitative approaches. The object of this study is the class teacher and 32 students of Grade III A of Elementary School Number 23 Marapalam, Padang. The findings show that the students’ intensive reading skill increased from 56,48% with 25% completeness percentage in Cycle I Meeting I to 70.12% with 56,25% completeness percentage in Cycle I Meeting II to 87,5% with 75% completeness percentage in Cycle II. The percentage increase from Cycle I to Cycle II is 30.1%. Thus, it is concluded that the SQ3R method can improve the intensive reading skill of Grade III students of Elementary School.                                                Keywords: Intensive Reading Skill; SQ3R Method